Serum Profile of Thyroid Hormones from Birth to Puberty in Buffalo Calves and Heifers - Ingole, Shailesh Dayaram; Deshmukh, B.T.; Nagvekar, A.S.; Bharucha, S.V. (Journal of Buffalo Science, 2012)
Growth is outcome of interactions among several factors, where thyroid hormones play a key role in coordination of these factors and the information of thyroid hormones in relation to growth in buffalo calves and heifers is not adequate. Thus the study was conducted on Murrah female buffalo calves and heifers, varying in age from newborn to 30 months. The study investigated the serum thyroid patterns in female Murrah buffalo calves and heifers from birth to puberty. The thyroid stimulating hormone concentration did not differ and remained almost the same from birth to 4 – 6 months. The thyroid stimulating hormone then gradually increased and reached a highest value at 24 – 30 months. The concentration recorded at 21 – 24 months and 24 – 30 month i.e. at the age of attaining the puberty, was about 3 – 4 times higher than recorded at birth. The T3 concentration recorded at 0 – 7 days of age was significantly higher than recorded for other age groups, except at 18 – 21 months, 21 – 24 months and 24 – 30 months. The T3 concentration did not exhibit specific trend during the ages 16 days – 1 month to 15 – 18 months. The highest T4 concentration was recorded in 0 – 7 days old buffalo calves. The concentration decreased to lower value at 1 - 2 months. The T4 concentration from 2 – 4 months of age increased significantly and the values remained almost similar with minor fluctuations upto 24 – 30 months. The T4: T3 ratio recorded at different ages did not exhibit specific trend